A BRIEF ANALYSIS OF THE PROS AND CONS OF ONLINE ADAPTIVE LEARNING AND EDUCATION - SEBASTIAN VAIDA (Studia Universitatis Babes-Bolyai, 2020)
ABSTRACT. Ever since ancient times, education has been a topic of interest for many civilizations. Seen as a means of progress, education was the main focus for some countries like Finland, and almost ignored by others. In the last decade, a new term has appeared in regard to education: adaptive learning. Used almost ubiquitous, the term has gained fame due to its presence in a 2013 program launched by the Gates Foundation, abbreviated ALMAP (Adaptive Learning Market Acceleration Program). This program changed into a grant that funded 14 higher education organizations to implement 9 adaptive learning products into 23 courses. The aim was to test and gather data on the impact of these programs of student outcomes. Almost instantly, the term became famous and used by many in their marketing and promotional strategies. In this brief analysis, we discuss the definitions, terminology, use, and pros and cons of adaptive learning in online education.